Стан розвитку державно-приватного партнерства у будівництві - Трач, Р. В. (Ways to Improve Construction Efficiency, 2014)
The article describes the most common classification of PPP in the implementation of infrastructure projects, examines the state of PPP in the construction of national highways and focuses on the need to intensify the process of the experience of the European Union.